Social and Psychological Readiness to Take Collective Action Against Violence Against Women: A Mixed Methods Study of Informal Settlements in Mumbai, India. (December 2021) - Gram, Lu; Chakraborty, Proshant; Daruwalla, Nayreen; Osrin, David
Past failures to mobilize communities in collective action against violence against women (VAW) have been ascribed to contextual challenges, but researchers have not systematically mapped community capacity for collective action against VAW. We conducted a mixed methods study in Mumbai, India using quantitative data from a household survey ( n = 2, 642) and qualitative data from 264 community meetings. We found attitudes supporting gender inequality and violence coexisted with significant enthusiasm and support for collective action against VAW. These findings open up avenues for policymakers to treat communities as less vulnerable and more capable of changing situations and problems that affect them.